2015
DOI: 10.1007/s00404-015-3647-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vitamin C, vitamin E, and molecular hydrogen on the placental function in trophoblast cells

Abstract: High levels of antioxidant vitamins C and E may have significant detrimental effects on placental function, as reflected by decreased cell viability and secretion of hCG; and placental immunity, as reflected by increased production of TNF-a. Meanwhile hydrogen showed no such effects on cell proliferation and TNF-α expression, but it could affect the level of hCG, indicating hydrogen as a potential candidate of antioxidant in the management of preeclampsia (PE) should be further studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…We and others have recently reported that hydrogen is also effective for pulmonary hypertension . The effects of hydrogen have been also reported in perinatal disorders: neonatal cerebral hypoxia; LPS‐induced fetal lung injury; preeclampsia; and perinatal brain injury caused by prenatal inflammation …”
Section: Introductionmentioning
confidence: 81%
“…We and others have recently reported that hydrogen is also effective for pulmonary hypertension . The effects of hydrogen have been also reported in perinatal disorders: neonatal cerebral hypoxia; LPS‐induced fetal lung injury; preeclampsia; and perinatal brain injury caused by prenatal inflammation …”
Section: Introductionmentioning
confidence: 81%
“…To the best of our knowledge, this is the only study so far where vitamin E, in the form of TRF from palm oil, demonstrated protection against PIH and preeclampsia. Other studies do not support the role of vitamin E in preventing either preeclampsia or PIH (18,(27)(28)(29)(30)(31)(32)(33)(34). However, the other studies used vitamin E in the form of the much weaker antioxidant tocopherol, either as a monotherapy or in combination with vitamin C.…”
Section: Discussionmentioning
confidence: 99%
“…The significant evidence of oxidative stress playing a key role in the development of preeclampsia directed to the hypothesis that antioxidant supplementation may have a role in preventing the disease. The potential of antioxidants such as vitamins C, E, selenium and lycopene (17) in the prevention of conditions associated with oxidative stress like preeclampsia, is supported by evidence-based studies (18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 98%
“…During embryo development and pregnancy, oxidative stress can lead to different tissue alterations and newborn diseases [253] [254]. The use of hydrogen as a possible therapeutic approach for diseases during pregnancy has been tested in vitro with trophoblast cell lines (JAR, JEG-3) [255]. This is important, as treatments with antioxidant vitamins (C and E) have been shown to be detrimental on placental function, as determined by decreased cell viability, decreased secretion of hormones and increased production of tumor necrosis factor-α.…”
Section: Hydrogen In Reproductive Tissues Pregnancy Neonatal Develomentioning
confidence: 99%
“…In contrast to vitamins, hydrogen does not cause any detrimental effects. Moreover, molecular hydrogen promoted the secretion of human chorionic gonadotrophin (hCG) by these cells, suggesting that hydrogen might be a suitable antioxidant for the management of diseases, such as preclampsia during pregnancy [255]. The administration of hydrogen to pregnant rats has been reported to be beneficial for ischemia/reperfusion injury and hippocampal damage in fetal rats [256].…”
Section: Hydrogen In Reproductive Tissues Pregnancy Neonatal Develomentioning
confidence: 99%